Genomic characterization of Bacillus cereus isolated from food poisoning cases revealed the mechanism of toxin production - Zhou, Qian; Li, Guanqiao; Cui, Yinshan; Xiang, Jingshu; Zhu, Shu; Li, Shijun; Huang, Jingyu; Wang, Yafang; Liu, Ying; Zhou, Li (Frontiers in Microbiology, 2024)
Bacillus cereus is a ubiquitous opportunistic human pathogen that causes food intoxications worldwide. However, the genomic characteristics and pathogenic mechanisms of B. cereus are still unclear. Here, we isolated and purified nine strains of B. cereus (LY01-LY09) that caused vomiting, diarrhea and other symptoms from four foodborne outbreaks happened in Guizhou Province in southwest China from June to September 2021. After colony observation, Gram staining, microscopic examination and biochemical test, they were identified as B. cereus. The genomic characteristics, phylogenetic relationships and virulence factors of the isolated strains were analyzed at the genome level. By genome sequencing, comparative genomic analysis, secondary metabolite analysis and quantitative PCR, we obtained the genome maps of LY01-LY09 and found that LY01-LY09 had a complex interspecific relationship with B. anthracis and B. thuringiensis. We also observed a contraction of gene families in LY01-LY09, and the contracted families were mainly associated with prophage, which contributed to the species diversity of B. cereus. The Hsp20 gene family underwent a rapid evolution in LY01-LY09, which facilitated the adaptation of the strains to adverse environmental conditions. Moreover, the LY01-LY09 strains exhibited a higher copy number in the non-ribosomal polypeptide synthetase (NRPS) genes and carried the complete cereulide synthetase (ces) gene cluster sequences. Considering that the NRPS system is a classical regulatory mechanism for emetic toxin synthesis, we hypothesized that LY01-LY09 could synthesize emetic toxins through the regulation of ces gene clusters by the NRPS system. These findings are important for further investigation into the evolutionary relationship between B. cereus and their related species, as well as the underlying mechanisms governing the synthesis and secretion of bacterial toxins.